The mediating role of job satisfaction in the relationship of vertical trust and distributed leadership in health care context. (9th May 2016) - Jain, Ajay K.
Abstract : Purpose: This study aims at investigating the effect of vertical trust on distributed leadership (DL) and performance as mediated by job satisfaction, and further to observe the role of DL in carrying out the effect of satisfaction on employees' performance. Design/methodology/approach: As grounded in the organizational citizenship behavior (OCB) literature, the author proposes that employees' participation in DL should be viewed as an extra role behavior, as leadership functions are not directly related to their job description. The study uses large-scale survey data from a study in one of Denmark's largest public hospitals ( N = 1, 439). Findings: The results of structural equation modelling (SEM) analysis showed that job satisfaction mediates the relationship between vertical trust and DL, and DL had a positive impact on job performance. Furthermore, the results showed that job satisfaction had a positive impact on DL and employees' performance. Moreover, DL has positively affected employees' performance, and it carries the impact of job satisfaction on performance. Research limitations/implications: The study showed that trust and job satisfaction are important triggers of DL. Furthermore, results are interesting because literature so far has shown an insignificant relationship between satisfaction and performance. Here, the author establishes that the satisfaction–performance relationship is mediated by DL. The findings should motivate health care organizations to introduce structures and educate formal leaders so that DL can be enabled. Originality/value: This should be the first study that relates trust and DL in an empirical manner. As grounded in the OCB literature, results also showed the significance of job satisfaction as a mediator variable.